Strategi Pemasaran Bisnis UMKM Sabun untuk Meningkatkan Perekonomian Masyarakat Desa Besar II Terjun - Andre Wahyudi; Nadlrah Naimi (Lembaga Pengembangan Kinerja Dosen, 2024)
Community Service Program (KKN) at the Faculty of Islamic Studies, University of Muhammadiyah North Sumatra is a community service program carried out individually with a cross-disciplinary approach. This study focuses on MSMEs in Desa Besar II Terjun, identifying problems related to product innovation and business marketing. Through a survey, the author found that many MSME actors have not been optimal in carrying out innovation and marketing, which has an impact on the community's economy. The results of the KKN activities show that students are able to build emotional connections with the community, help MSME actors, and provide a new atmosphere in the village. Supporting factors for activities include family and community support, while inhibiting factors are more internal, such as lack of motivation. These findings emphasize the importance of business innovation and marketing in improving the community's economy and the contribution of students in developing MSMEs.